1975
DOI: 10.1042/bj1500123
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of gluconate by Escherichia coli. A role of adenosine 3′:5′-cyclic monophosphate in the induction of gluconate catabolism

Abstract: 1. Cultures of Escherichia coli growing on gluconate use both gluconate and glucose when glucose is added. 2. Glycerol-grown cells adapt to gluconate utilization even in media containing glucose as well as gluconate. 3. The rates of gluconate utilization by cells growing on a mixture ofglucose and gluconate, and the specific activities ofthe gluconate uptake system and of gluconate kinase, are greater if adenosine 3': 5'-cyclic monophosphate (cyclic AMP) is present in the medium than in its absence. 4. Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…The modest catabolite repression of gntKU transcription (4-fold), by virtue of a CAP-binding site at the gntK promoter, confirms measurements of gluconokinase and gluconate transport made by others (2). It is quite interesting that gntK and gntU are subject to glucose catabolite repression, considering that gluconate is deemed to be more catabolite repressing than glucose (30).…”
Section: Vol 178 1996supporting
confidence: 51%
See 2 more Smart Citations
“…The modest catabolite repression of gntKU transcription (4-fold), by virtue of a CAP-binding site at the gntK promoter, confirms measurements of gluconokinase and gluconate transport made by others (2). It is quite interesting that gntK and gntU are subject to glucose catabolite repression, considering that gluconate is deemed to be more catabolite repressing than glucose (30).…”
Section: Vol 178 1996supporting
confidence: 51%
“…It has long been thought that the high-affinity gluconate transporter encoded by gntT plays a primary role in gluconate metabolism, as does gntK, which encodes the primary gluconokinase (2,33). Previous reports indicate that the high-affinity (GntT) gluconate transporter is induced for growth on gluconate while the lowaffinity transporter (GntU) is not (14,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative branches consist of: (1) PTSmediated glucose transport, or (2) glucose oxidation to gluconate and subsequent transport, phosphorylation and catabolism via the gluconate-inducible Entner-Doudoroff pathway. This pathway would of course be functional only in the absence of catabolite repression of the Entner-Doudoroff enzymes, which has been reported [44]. Eisenberg and Dobrogosz [34] showed that gluconate and glucose can be degraded simultaneously by E.…”
Section: Inducible Linear Pathwaymentioning
confidence: 81%
“…E. coli gntT mutants are severely affected in the utilization of gluconate; moreover, some E. coli bioH-asd deleted mutants are unable to grown on this substrate (NAGEL DE ZWAIG et al 1973, FAIK and KORNBERG 1973ISTURIZ et al 1979. These and other observations suggested the GntI and GntII systems involved as main and subsidiary respectively, in the capture and phosphorylation ofgluconate (BACHI and KORNBERG 1975 a).The GntI and GntII activities convert external gluconate to intracellular 6-phosphogluconate, which can either be decarboxylated to pentose-phosphate by the action of the enzyme 6-phosphogluconate dehydrogenase (EC 1.1.1.44., gene gnd) or metabolized to pyruvate and glyceraldehyde 3-phosphate via the ENTNER-DOUDOROFF pathway (EISEN-BERG and DOBROGOSZ 1967). The first enzyme involved in the latter pathway, 6-phosphogluconate dehydratase (EC 4.2.1.12., gene edd), as well as the GntI and GntII activities are induced when the cells are cultivated in gluconate-containing media (COHEN 1951, FRAENKEL and LEVISOHN 1967, NAGEL DE ZWAIG et a/., 1973, POUYSS~GUR et a/.…”
mentioning
confidence: 95%